The Institutional Foundations of the Digital Economy in the 21st Century - Abramov, Aleksandr N.; Adamchuk, Natalia G.; Afonin, Petr N.; Ageeva, Olga A.; Ainous, Shaker; Alekseev, Alexander N.; Alpidovskaya, Marina L.; Bank, Olga A.; Bank, Sergey V.; Baranovskaya, Tatyana P.; Beksultanov, Azisbek A.; Belous, Nikolai M.; et al. (Interdisciplinary Thought of the 21st Century ;, 2021)
The development of the Digital Economy has been a landmark breakthrough for economic systems in the 21st century, as it opens up opportunities for the full-scale implementation of new digital technologies and the optimization of economic activities. While the conceptual essence and specific features of the digital economy are described in detail in the existing literature, the practical foundations of its formation are poorly studied. In this book, the digital economy is studied from the perspective of neo-institutional economic theory. This allows for the tracking of the process of formation (institutionalization) of the digital economy, determining the basic institutions that are necessary for its formation and that exist in modern economic practice, and analyzing scenarios for the future development of the digital economy in the 21st century.